Realization of speech in design intent of geometric modelling - B P, Sreeja; K G, Amrutha; Benedicta J, Jeni; V, Kalaiselvi; R, Ranjani (International Journal of Engineering and Technology, 2017)
The conventional interactive mode is especially used for geometric modeling software. This paper describes, a voice-assisted geometric modeling mechanism to improve the performance of modeling, speech recognition technology is used to design this model. This model states that after receiving the voice command, the system uses the speech recognition engine to identify the voice commands, then the voice commands identified are parsed and processed to generate the geometric design based on the users voice input dimensions, The outcome of the system is capable of generating the geometric designs to the user via speech recognition. This work also focuses on receiving the feedback from the users and customized the model based on the feedback.